PENGARUH KEPEMIMPINAN, KEMAMPUAN KERJA DAN MOTIVASI TERHADAP KINERJA PERSONEL BINTARA DINAS KESEHATAN TNI ANGKATAN LAUT DAN UNSUR PELAKSANA TEKNIS (UPT) WILAYAH JAKARTA - Ida Ayu Nyoman Putranti; Ahmad Faisal (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2021)
Abstract : This research aims to examine and analyze the effects of leadership, ability, and motivation on employee performance of Warrant officers and non-commissioned personnel (Case study at Indonesian Navy Health Service). The method of research is a quantitative approach. Data of research is primary data for observation from April up to August 2020. The number of samples of this research was 94 respondents, consists of all Warrant officers and non-commissioned personnel levels. The method used in this research is path analysis, which previously used the instrument test in the questionnaire, namely by testing the validity and reliability, then testing the analysis requirements, namely the normality test, significance test, and linearity test. After that, the hypothesis is tested. The conclusions of the research results are as follows: Leadership has a positive effect on motivation, the ability has a positive effect on motivation, leadership has a positive direct effect on performance, the ability has a direct positive effect on performance, motivation has a direct positive effect on performance, Leadership, Ability, and Motivation together have a positive effect on the performance of the Indonesian Navy Health Service personnel.Keywords : Leadership, Ability, Motivation, and Employee’s Performance